2023
DOI: 10.1186/s12936-023-04452-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers against and strategies for malaria control during the COVID-19 pandemic in low- and middle-income countries: a systematic review

Abstract: Background The COVID-19 pandemic has disrupted malaria control activities globally. Notably, high levels of excess malaria morbidity and mortality in low- and middle-income countries (LMICs) were reported. Although it is crucial to systematically understand the main causes of the disruption to malaria control and synthesize strategies to prepare for future pandemics, such studies are scarce. Therefore, this study aims to better identify barriers against and strategies for malaria control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Coupled with the recent slow progress in malaria reduction in SSA, the recent global pandemic—coronavirus disease (COVID-19)—has further contributed to the interruption of malaria control undertakings in malaria endemic regions of the world. Park et al 7 reported the high levels of surfeit malaria morbidity and mortality in Low and Middle Income Countries (LMICs), which could be attributed to poor community engagement and limited malaria tests. For example, the work of Ilesanmi, Afolabi and Iyiola 8 identifies limited acquisition of malaria tests to healthcare providers as a barrier against visiting health facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with the recent slow progress in malaria reduction in SSA, the recent global pandemic—coronavirus disease (COVID-19)—has further contributed to the interruption of malaria control undertakings in malaria endemic regions of the world. Park et al 7 reported the high levels of surfeit malaria morbidity and mortality in Low and Middle Income Countries (LMICs), which could be attributed to poor community engagement and limited malaria tests. For example, the work of Ilesanmi, Afolabi and Iyiola 8 identifies limited acquisition of malaria tests to healthcare providers as a barrier against visiting health facilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the World Health Organization (WHO) recently reported 247 million malaria cases in 2021, as against 245 million cases reported in 2020 and 231 million cases in 2019. This marked increase might be partly due to the COVID-19 pandemic, which caused interruptions of malaria control interventions in many malaria-endemic countries [ 3 ], as funds for malaria control were diverted to curtail the effects of the pandemic in low and middle income countries [ 4 , 5 ]. WHO estimates indicate that African regions have the largest malaria burden in the world, accounting for 95% of cases and 96% of deaths from the disease, with children under the age of five accounting for 80% of these deaths [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Unfortunately, the COVID-19 pandem-ic has disrupted aid campaigns and control efforts, exacerbating the situation. [3,4] As a result, new programs have been launched to reduce malaria incidence and mortality by 2030. [5] Preventive therapies may include vaccines such as RTS,S/AS01 or schizonticidal agents such as Malarone (atovaquone + proguanil), chloroquine (Figure 1), a broad-spectrum antimalarial agent whose efficacy is dramatically decreasing in the last years due to the rise of resistant phenotypes, and artemisinins (Figure 1), depending on the specific species of the infecting protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021 alone, World Health Organization (WHO) estimated that there were more than 200 million cases of malaria worldwide, resulting in around 600,000 deaths [2] . Unfortunately, the COVID‐19 pandemic has disrupted aid campaigns and control efforts, exacerbating the situation [3,4] . As a result, new programs have been launched to reduce malaria incidence and mortality by 2030 [5] .…”
Section: Introductionmentioning
confidence: 99%